The Effects of Creative Visual Content, Affiliate Marketing, and Influencer Marketing on Consumer Purchase Intention - Raehan Ferdian Putra; Erwin Permana (International Journal of Business Studies, 2026)
This study aims to examine the influence of creative visual content, affiliate marketing collaboration, and influencer marketing on consumer purchase intention toward the Rucas.co brand. The research adopts a quantitative approach using a survey method with 100 respondents who are active social media users and have been exposed to creative content, affiliate promotions, or influencer endorsements related to the brand. Data were analyzed using multiple linear regression analysis to test both partial and simultaneous effects of the independent variables on purchase intention. The results reveal that creative visual content, affiliate marketing collaboration, and influencer marketing each have a positive and significant effect on consumer purchase intention. Simultaneously, the three variables significantly explain variations in purchase intention, with an Adjusted R² value of 0.781, indicating strong explanatory power. Among the independent variables, influencer marketing has the most dominant effect. These findings suggest that an integrated digital marketing strategy combining visually engaging content, credible influencers, and structured affiliate collaboration plays a crucial role in shaping consumer purchase intention. This study contributes to the digital marketing literature by providing empirical evidence on the effectiveness of social media-based promotional strategies for local fashion brands and offers practical insights for businesses in optimizing their online marketing efforts.